The r(20) syndrome. Issue 4 (August 1977) - Herva, R; Saarinen, I; Leikkonen, L
Abstract : A 21-year-old woman with a ring-20 chromosome is described. The clinical findings, behaviour problems, epilepsy, and low grade mental retardation are the same as in the 3 cases described earlier. It seems to be justified to speak of a specific ring-20 syndrome.